Educational processes of training, retraining and advanced training of private detectives in Ukraine - Anatolii, Kyslyi; Pysmenna, Mariia; Kolomoiets, Oleksandr; Volobuieva, Olena; Davydenko, Valerii (Cuestiones Políticas, 2020)
The aim of the article was to carry out a retrospective analysis of the legal acts on the legalization of private detective activities in Ukraine and, at the same time, consider the characteristics of training, retraining and advanced training of private detectives in order to to further improve legislation in this area. The subject of the study is essentially the process of training, retraining and advanced training of private detectives in Ukraine. During the research, the following scientific methods were used: dialectical method, methods of synthesis and analysis, methods of induction and deduction, statistical method, historical and legal and formal and legal methods. The peculiarities of the Law of Ukraine "On the Activity of Private Detective (Search)" were considered, its advantages and disadvantages were described. By way of conclusion, he emphasizes that the existing legal education system, introduced in civil educational institutions, is not adequate for the training of private detectives. For these and other political and legal reasons, the need to train private detectives in the system of higher education institutions with specific learning conditions in the heat of the requirements imposed by reality itself is argued.